Rethinking Representations of Asian Women Changes, Continuity, and Everyday Life - Ijichi, Noriko; Kato, Atsufumi; Sakurada, Ryoko; SpringerLink (Online service) (New York : Palgrave Macmillan US (Imprint), 2016)
Based on historic and ethnographic approaches, this volume examines how the ideological images of Asian women are produced, circulated, appropriated, and pluralized. Contributors analyze the interactions between the politicized formation of ideological representations and the everyday practices of women who resist and re-contextualize these images.
Keywords: Culture-Study and teaching; Anthropology; Communication; Ethnicity